PENGELOLAAN DATA DAN DOKUMEN IMPOR DALAM MENDUKUNG EFISIENSI LOGISTIK DI PT DANISINDO SEMESTA LOGISTIK BATAM - Nurfita, Rinda; Khadijah , Khadijah; Fadlilah , Andi Hidayatul (PUAN INDONESIA, 2025)
This community service program aims to enhance the skills of employees at PT. Danisindo Semesta Logistik Batam in digitally managing import data and documents to support logistics efficiency. The main challenges faced by the company include the lack of an integrated system for recording and storing import documents and low digital literacy among administrative staff. The program was implemented using a participatory approach, case-based training, and direct mentoring. The results indicate improvements in data accuracy, faster administrative processes, and reduced risks of data loss or duplication. This educational initiative is expected to have a long – term impact on building an efficient and integrated logistics system within the company.